Exercise Frequency and Fracture Risk in Older Adults-How Often Is Enough? - Kemmler, Wolfgang; von Stengel, Simon; Kohl, Matthias (Current Osteoporosis Reports, 2017)
PURPOSE OF REVIEW: Due to older people's low sports participation rates, exercise frequency may be the most critical component for designing exercise protocols that address fracture risk. The aims of the present article were to review and summarize the independent effect of exercise frequency (ExFreq) on the main determinants of fracture prevention, i.e., bone strength, fall frequency, and fall impact in older adults. RECENT FINDINGS: Evidence collected last year suggests that there is a critical dose of ExFreq that just affects bone (i.e., BMD). Corresponding data for fall-related fracture risk are still sparse and inconsistent, however. The minimum effective dose (MED) of ExFreq that just favorably affects BMD at the lumbar spine and femoral neck has been found to vary between 2.1 and 2.5 sessions/week. Although this MED cannot necessarily be generalized to other cohorts, we speculate that this "critical exercise frequency" might not significantly vary among adult cohorts.
EVALuna2:33275